Design of VHDL for MPPT Incremental Conductance on FPGA with Altera DE2-115 Development Board for Educational Purposes - Virbora Ny; Channareth Srun; Phok Chrin; Sokchea Am; Bunthern Kim; Saran Meas (Universitas Pendidikan Indonesia (UPI), 2024)
In this paper, the design of VHDL for MPPT Incremental Conductance on an FPGA with the Altera DE2-115 Development Board is presented for educational purposes. The FPGA is programmed to control the MPPT tracking process by obtaining the maximum power from the solar panel. The Altera DE2-115 Development Board is used for the FPGA system design. The system is designed for individual blocks that are designed specifically to operate each step in the MPPT process. The system consists of five main parts: the solar panel, ADC, FPGA, PWM, and DC-DC Boost Converter. The solar panel provides the DC voltage and current. The ADC converts the solar panel's constantly changing voltage and current to a digital signal. The INC algorithm is started after the FPGA receives the digital signal from the ADC. The output PWM from the MPPT algorithm will drive the DC-DC Boost Converter circuit for the solar power tracking process. The experimental results show that the designed system can track the maximum power point of the solar panel.